(untitled) (INFERENCE: Journal of English Language Teaching, 2026)
This study aims to analyze the translations of idioms from English into Indonesian in The Mortal Instruments: City of Bones novel, through examining three specific aspects: idioms identification, translation strategies, and translation accuracy. A qualitative approach by content analysis was employed for data collection and analysis. The findings revealed 53 idioms in the Source Text (ST). The result of this study shows that only two out of six translation strategies were implemented. Paraphrasing was the most frequently applied strategy; by contrast, omission of the entire idiom strategy occurred least often. Additionally, other strategies were also observed beyond the framework, namely, literal translation and mistranslation. The majority of the idioms’ intended meaning are accurately retained and classified as accurate in the target text. In conclusion, the application of paraphrasing in novels consistently proves its efficacy in achieving accuracy that maintains intended meaning.